Factors significancy when determining the flexion of welded girders with increased one zone's width - Palić, Vlastimir (Journal of Production Engineering, 2023)
In this paper, the significance of factors was investigated when determining the flexion of welded girders, specifically in cases where the width of one zone was increased by 50%. The thickness of the sheet girder's metal was 6 mm.